2006
DOI: 10.1590/s0101-20612006000200017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de diferentes híbridos suínos submetidos à insensibilização elétrica e gasosa (CO2): parte 2 - mensurações objetivas de qualidade

Abstract: O desenvolvimento das anomalias PSE e DFD na carne suína é fruto de interação entre o genótipo e o ambiente. Portanto, os procedimentos de abate por si constituem fatores estressantes muito fortes para os animais. Embora a insensibilização elétrica tenha sido muito difundida desde o final da década de 1920, o aspecto humanitário da insensibilização com CO 2 ainda é um assunto muito controvertido dentro da comunidade científica. Esta técnica de insensibilização vem ganhando muita popularidade na comunidade euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…However, our results also showed an increase in the blood lactate level between RE and EX (P < 0.001; Figure 1), meaning that electrical stunning may have an impact on the rate of lactate release into the blood flow at slaughter in this study. Greater blood lactate levels have also been reported in electrically v. gas stunned pigs by Bertoloni et al (2006). This difference can be explained by the greater muscle contraction (tonic phase) in response to electrical current application.…”
Section: Resultsmentioning
confidence: 88%
“…However, our results also showed an increase in the blood lactate level between RE and EX (P < 0.001; Figure 1), meaning that electrical stunning may have an impact on the rate of lactate release into the blood flow at slaughter in this study. Greater blood lactate levels have also been reported in electrically v. gas stunned pigs by Bertoloni et al (2006). This difference can be explained by the greater muscle contraction (tonic phase) in response to electrical current application.…”
Section: Resultsmentioning
confidence: 88%
“…Para as avaliações de perda por exsudação e capacidade retenção de água (CRA), foram utilizadas amostras em duplicatas do músculo Longissimus dorsi, entre a 2 a e a 4 a vértebra torácica, num período de 24h post-mortem. A avaliação da perda por exsudação foi baseada na suspensão da amostra em sacos plásticos inflados, sob atuação da gravidade, conforme metodologia descrita por HONIKEL (1998) e a capacidade de retenção de água foi realizada segundo a metodologia descrita por BERTOLONI et al (2006b).…”
Section: Methodsunclassified
“…The results from these papers showed that the animals stunned with the gaseous stunning system presented results for the following indicators of animal welfare and carcass and meat quality: plasmatic levels of cortisol and lactate (Bertoloni, Silveira, Ludtke, & Andrade, 2006); b* value, pH 24 h in the semimembranosus muscle, light scattering (Hennessy-GP4) to 45 min and 24 h post mortem ; and bloodsplash, skin damage and eyelid reflex levels than the electric stunning system. The authors reported variation among the genetic strains for some of indicators evaluated, suggesting the occurrence of genotype-environment interactions for those traits.…”
Section: Characterisation Of Pre-slaughter Management In Brazil Chilmentioning
confidence: 99%